Borrelia burgdorferi sensu lato in Ixodes ricinus ticks from Norway: evaluation of a PCR test targeting the chromosomal flaB gene - Jenkins, Andrew; Hvidsten, Dag; Matussek, Andreas; Lindgren, Per-Eric; Stuen, Snorre; Kristiansen, Bjørn-Erik (Experimental and Applied Acarology, 2012)
A consensus TaqMan real-time PCR test targeting the chromosomal flaB gene of Borrelia burgdorferi sensu lato was constructed. The test was compared with a recently published generic Light Upon eXtension (LUX) 16S rRNA real-time PCR test (Wilhelmsson et al. in J Clin Microbiol 48:4169–4176, 2010) on material consisting of 242 Ixodes ricinus ticks collected from dogs and cats in Northern Norway (n = 139) and Telemark County in Southern Norway (n = 103). Ticks positive in either test were further tested by nested PCR amplification of the 5S-23S rRNA intergenic-spacer region followed by sequencing for species identification. A tick was defined as Borrelia positive if two of three tests were positive. Thirty-four of the 242 (14 %) ticks satisfied this definition of positivity. Of these ticks 32 were positive both in the rRNA and flaB test, while two were positive only in the rRNA test. One tick was positive only in the rRNA test and was considered false positive since PCR for sequencing failed. The sensitivity of the flaB test was 94 % and the specificity 100 %. It was possible to determine the species present using Tm analysis. Among ticks from Northern Norway the prevalence of Borrelia was 13 %, whereas the prevalence in Telemark was 16 %. Among identified species (n = 33) B. afzelii was found in 16 (47 %), B. garinii in 15 (44 %) and B. valaisiana in 2 (6 %) ticks, respectively. The flaB test is a rapid, sensitive and specific test for detection and quantification of Borrelia burgdorferi s.l. in I. ricinus ticks. This is the first report on Borrelia prevalence in I. ricinus in Northern Norway.